Resolving anticipatory grief and enhancing dignity at the end-of life : a systematic review of palliative interventions - Patinadan, Paul Victor (2021)
Anticipatory grief is the experience of grief symptomatology prior to loss. This study is a systematic review of empirical interventions or interventional components that were observed to lessen or adaptively direct the experience of anticipatory grief for patients at the end of life and their family members. A search of 5 major databases found 13,718 articles, of which 10 high-quality randomized controlled trials were included for final review. Lebow’s “adaptational tasks of anticipatory mourning” was employed as a working model on the efficacy of the interventions. The interventions exhibited some positive outcomes but none addressed anticipatory grief directly. Recommendations for future research are discussed.